Case Report: A New Entity: Multiple Differentiated Variant of Papillary Thyroid Carcinoma With Advanced Clinical Behavior - Yang, Jing; Gong, Rixiang; Ma, Yu; Gao, Jun; Li, Zhihui; Zhu, Jingqiang; Gong, Yanping (Frontiers in Endocrinology, 2021)
There are many histological morphological types of papillary thyroid carcinoma (PTC), but the most frequently seen types are conventional. A single PTC commonly has a conventional and/or a variant morphological pattern. PTC with multiple (more than two) well-differentiated morphological patterns are extremely rare. We herein report the rare case of a 48-year-old male with initial diaphragmatic, pancreatic, and liver tumors from PTC. Then, the PTC was discovered following resection of these tumors, an ultrasound-guided fine-needle aspiration (US-FNA) cytology of a huge mass in the thyroid’s left lobe revealed a PTC. After postoperative recovery, physical and ultrasound examinations identified an irregular large nodule in the thyroid's isthmus and left lobe, several swollen lymph nodes in the left neck, a mass in the left gluteus maximus, and several masses in both the bilateral parotid and salivary regions. The US-FNA’s pathological examination confirmed metastatic PTCs in the left gluteus maximus and bilaterally in the parotid and salivary glands. An 18-fluorodeoxyglucose positron-emission tomography and computed tomography scan revealed abnormal uptakes in numerous locations (e.g., thyroid's isthmus and left lobe, bilateral parotid gland, and subcutaneous tissues). The patient underwent palliative therapy—including total thyroidectomy, bilateral central neck dissection, left lateral neck dissection, and excision of the bilateral parotid and salivary glands. A whole-body scan post-therapeutic radioactive iodine ablation revealed exclusive thyroid bed uptake. The patient subsequently underwent thyroid stimulating hormone (TSH) repression therapy and chemotherapy with lenvatinib, and thereafter achieved stable clinical conditions. Further histopathological analysis of the PTC revealed multiple differentiated morphological patterns in the single tumor located in the isthmus and left lobe of the thyroid, and in some metastatic lesions. Different metastatic lesions also presented different morphological patterns of PTC. In conclusions, we identified a new entity of PTC as a multiple differentiated variant of PTC (MDV-PTC) with an aggressive clinical nature.